Coupling agents and biomimetic methods of calcium hydroxyapatites design as basic elements of the hierarchically structured bone scaffold - Jokanović Vukoman; Čolović Božana; Marković Zoran (Serbian Medical Society - Dental Section, Belgrade, 2009)
In this paper, various modifications of agent coupling and biomimetic methods of synthesis and design of calciumhydroxyapatites as basic elements of the hierarchically structured bone scaffold are described. These elements are created to have a very strictly defined geometry and phase composition, which can have essential importance for the morphology and geometry design of the bone scaffold thin inner walls, with strong influence to the bone cell activity and their balance during the processes of bone modeling and remodeling. Different kind of these methods for synthesis basic elements, e.g. calcium hydroxyapatite, as constitutive elements of the scaffold inner walls with their specific design from the aspects of the size and shape of their particles are the key factors in the processes of the tissue engineering and osteointegration of these materials used as building blocks of scaffold structure.